Are they problem learners or students with learning disabilities? What do teachers know about LD? - Doyran, Feyza; Canca, Irene (My University, 2013)
This research investigated the level of awareness and existing knowledge processed by general education instructors and counselors in a private school system regarding learning disabilities (LD) in Istanbul, Turkey. General education instructors who teach students from the age range of 5-19 in all subjects including English as Foreign Language practitioners as well as counselors who work with this population are the focus of this study. The main purpose of this study is to elicit current knowledge levels of learning disabilities awareness among teachers currently practicing in private school systems. The subsidiary purpose is to discern if learning disabilities in general or the targeting of specific disabilities should be the focus of training workshops and seminars. This study, therefore, is the first step of a needs analysis on this specific topic. One hundred participants who are currently working in this private school sector have completed a 25 question survey which was developed and piloted by Dr. Sheila Saravanabhaven of Virginia State University and Dr. RC Saravanabhaven of Howard State University and published in the International Journal of Special Education (vol. 25, no. 3, 2010). Permission for its use has been granted with the original survey to be administered. Additionally, the counselors currently administering to this populous were interviewed and asked specific questions regarding their preparation in the area of learning disabilities. The quantitative data were analyzed using SPSS and for the open-ended questions content analysis was applied. The analysis pointed to some discrepancies among awareness levels of educators with the focus of examination on pre-service courses required while pursuing a degree in Education as well as professional development exposure regarding learning disabilities awareness. The results of this study together with its implications on teaching and learning process show that in order to gain more awareness there is a need for teachers of all subjects to go through training workshops and seminars focusing on various types of learning disabilities which would eventually affect their student body. Special Education courses in the undergraduate teacher education programs should also put more emphasis on these issues.

Bu araştırma, İstanbul ilindeki özel okullarda görev yapmakta olan öğretmenlerin özel (özgül) öğrenme güçlükleri ile ilgili farkındalık seviyelerini ve bu konu hakkındaki bilgi düzeylerini belirlemek üzere yapılmıştır. Araştırmanın hedef kitlesi, 5-19 yaş arası öğrenciye hitap eden aralarında İngilizce öğretmenlerinin de olduğu her alandan öğretmen ve rehber öğretmendir. Araştırmanın başlıca amacı, özel okul sektöründe çalışmakta olan öğretmenlerin öğrenme güçlükleri konusunda hali hazırda sahip oldukları bilgi düzeylerini belirlemektir. Bir diğer amaç ise, öğretmenlerin hizmetiçi eğitimlerinde öğrenme güçlükleri konusunun üzerinde durulması gereği olup olmadığıdır. Yani, başka bir değişle, bu çalışma bu konudaki bir ihtiyaç analizi niteliğindedir. Virginia State University’den Dr. Sheila Saravanabhavenve Howard State University’den Dr. RC Saravanabhaven tarafından geliştirilip, pilot uygulamaları, geçerlik ve güvenirlikleri de yapılarak, the International Journal of Special Education (vol. 25, no. 3, 2010) dergisinde basılan 25 soruluk anketin kullanım izinleri alınmış ve original ankete ulaşılarak İstanbul’da özel okullarda çalışmakta olan 100 öğretmene anket uygulanmıştır. Ayrıca, aynı grupta görev yapmakta olan rehber öğretmenlerle de yüz-yüze mülakatlar yapılmış ve kendilerine öğrenme güçlükleri ile ilgili yaptıkları hazırlıklar, edindikleri bilgiler sorulmuştur. Nicel verilerin analizinde SPSS programı, nitel verilerin analizinde ise içerik analizi yöntemi kullanılmıştır. Yapılan analizler sonucunda, eğitimcilerin öğrenme güçlükleri konusundaki farkındalık seviyelerinde farklılıkların bulunduğu belirlenmiştir. Araştırmanın sonucunda, öğretmenlerin bu konuda daha çok farkındalığa sahip olabilmeleri için eğitimler almaları gerektiği, lisans programlarında bu konunun, Özel Eğitim gibi derslerde, daha derinlemesine işlenmesi gerektiği ortaya çıkmıştır.
Sorunllu Öğrenci Mi, Öğrenme Güçlüğü Olan Öğrenci Mi? Öğretmenler Öğrenme Güçlükleri Hakkında Ne Biliyorlar?
Keywords: Learning Disabilities; Private School Teachers; Special Education; Özel (Özgül) Öğrenme Güçlükleri; Özel Okul Öğretmenleri; Özel Eğitim